KONSEP PENGEMBANGAN KURIKULUM TAHFIZH AL-QUR’AN DI PONDOK PESANTREN - Abu Maskur (Fakultas Tarbiyah Institut Ilmu Al-Qur'an (IIQ) Jakarta, Indonesia, 2022)
The background of this research is that the curriculum is a tool that can be used to achieveeducational goals so that the curriculum cannot be separated from the educational process. Thepurpose of this research is to find out the role of the tahfiz curriculum and the concept ofdeveloping the tahfiz Al-Qur'an curriculum in Islamic boarding schools. This research is a type ofconcept analysis research or concept analysis in which the data source is based on literature review(literature study). Researchers collected data by means of documentation, namely one method ofcollecting data qualitatively by viewing or analyzing documents made by the subject himself or byother people about the subject. The results of this research state that in developing the Al-Qur'antahfizh curriculum, Islamic boarding schools must pay attention to various aspects related to thecurriculum, namely the foundations, principles, and curriculum development steps. Thefoundations in developing the Al-Qur'an tahfizh curriculum in Islamic boarding schools includephilosophical, psychological, and sociological foundations. Then, the principles that must beconsidered in developing the Al-Qur'an tahfizh curriculum in Islamic boarding schools include theprinciples of relevance, flexibility, continuity, practice, and effectiveness. While the steps indeveloping the Al-Qur'an tahfizh curriculum in Islamic boarding schools include three coreactivities, namely planning, implementing and evaluating curriculum development.